Teaching new tricks to old dogs: A review of drug repositioning of disulfiram for cancer nanomedicine. Issue 4 (10th February 2021) - Zhao, Pengfei; Tang, Xueping; Huang, Yongzhuo
Abstract: The increasing incidence and mortality of malignant tumors have required the development of diversified innovative therapies. Compared with the new therapeutic molecule invention, it is a more economical and efficient way to reposition old drugs that have been marketed or in clinical trials for tumor treatment. Studies have been carried out for repositioning the old approval drugs that are widely applied clinically with reliable biosafety and effectiveness evidence, including aspirin, artemisinin (and its derivatives, eg, dihydroartemisinin), metformin, and disulfiram (DSF). In addition to the approved pharmacological activity, these old drugs exhibited broad tumor‐suppressive effects. This review summarizes the drug repositioning strategy of DSF through nanotechnology and outlines the DSF nano‐formulations for cancer targeting delivery and therapy. Abstract : Repurposing disulfiram for cancer therapy has attracted great interest. By using advanced delivery techniques, DSF‐based nanomedicines can achieve tumor‐targeted delivery and controlled release, thus providing a promising solution to enhance treatment efficacy. Nanomedicine‐mediated codelivery also offers a useful strategy for DSF‐based combination therapy. Many efforts have been made to repurposing disulfiram due to the extensive anti‐tumor activity and biosafety. By using advanced delivery techniques, DSF‐based nanomedicine would achieve targeted delivery and spatiotemporal controlled release, thus providing a potential solution to address the 3R principle (right place, right dose, and right time) to maximize the efficacy of cancer therapy.